EC(H)O-NARRATING STORIES: Ecological Thought and Metanarrativity in Folktales - Jayagopalan, Gaana (Journal of Dharma, 2014)
This paper studies the ecological discourse constructed in folktales, looking at the relationship between folktales and the human-nature-culture paradigm. By closely examining select folktales collected by folklorist A. K. Ramanujan, this paper looks at the metanarrativity of tales and argues from a narratological perspective that folktales deploy nature metaphors to establish a close relationship between nature, women and culture. This, it is argued, is made possible only in the conservation of stories for, in conserving a story, the message of conserving cultures and their artefacts (an ecological metaphor) is spread. The story is conserved; however, not in hoarding it but quite contrarily in transmitting and letting it go. The paper also critically examines how female subjects, through the use of nature metaphors and symbols of fertility and femininity speak of their consciousness in these ‘woman-centred tales’ in a space characterized by the absence of the Phallic Other but inevitably speak the patriarchal language of feminine inscriptions. Using folkloric research of A. K. Ramanujan as well as ecocritical frameworks, this paper looks at the narratological dimensions of folklore to understand metanarration as a crucial aspect of folklore and ecological conservation. Therefore the lessons of conservation lie not only in the content of the folktales but also in their very telling. The ecological aspects in and of the tale must necessarily be echoed multiple times to enable the tale’s transmission, and in effect, their conservation.